Kin Ties and the Performance of New Firms: A Structural Approach - Ertug, Gokhan; Kotha, Reddi; Hedström, Peter (Academy of Management Journal, 2020)
Kin ties are all but ubiquitous in new firms. However, their effects on performance are not straightforward, as they can provide new firms with advantages (enhanced coordination and cooperation) as well as disadvantages (reduced diversity, nepotism concerns, and the possible spillover of personal conflict). As kin ties may have both positive and negative implications for performance, a contingency approach to the performance of new firms is valuable. We develop such an approach by relating different structural configurations of kin ties—whether they are between founders, between founders and employees, or between employees—to the performance of new firms. We test our predictions using data on 4,967 new firms founded in Stockholm between 1998 and 2003. Our theory deepens our understanding of why kin ties have heterogeneous effects on the performance of new firms.